(-16+3x5-10+13) : (17-16-3) =
{(-18) : (-6) x (-2) - (-3) x [ 20+(-4) x (-5)]} : (-57)
Va rog ajutatima!!
Răspunsuri la întrebare
Răspuns de
0
(-16+3x5-10+13):(17-16-3)=
(-16+15-10+13):(-2)=
(-1-10+13):(-2)=
(-11+13):(-2)=
2:(-2)=
-1
(-16+15-10+13):(-2)=
(-1-10+13):(-2)=
(-11+13):(-2)=
2:(-2)=
-1
ioanabeatryce3:
{(-18):(-6)x(-2)-(-3)x[20+(-4)x(-5)]}:(-57)=
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă